Bromido(1,4,7,10,13-pentaazacyclohexadecane)cobalt(III) dibromide dihydrate - Kurisaki, Tsutomu (International Union of Crystallography, 2013)
The title salt, [CoBr(C(11)H(27)N(5))]Br(2)·2H(2)O, contains a complex cation with mirror symmetry and two Br(−) counter-anions that are likewise located on the mirror plane. The central Co(III) atom of the complex cation has one Br(−) ion in an axial position, one N atom of the pentadentate macrocyclic ligand in the other axial position and four N atoms of the ligand in equatorial positions, defining a distorted octahedral coordination geometry. The macrocyclic ligand is coordinated to the Co(III) atom within a 5, 6, 5 arrangement of chelate rings in the equatorial plane of the four N atoms. Due to symmetry, the configuration of the chiral N atoms is 1RS, 4SR, 10RS, 13SR. In the crystal, N—H⋯Br, O—H⋯Br and N—H⋯O hydrogen bonds between the complex cation, anions and lattice water molecules generate a three-dimensional network.